PERLINDUNGAN HUKUM BAGI ANAK DI ERA OTONOMI DAERAH (Studi tentang Peran Pemerintah Daerah dalam Mengatasi Masalah Pekerja Anak) - Agus Triono (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2014)
The State plays a role and is responsible for the provision of protection in children, including the fulfillment of children's rights. But organizers of both Government and state, local governments still lack the attention and protection of the child. In the province of Lampung, children who work under is still very high, the national team is the acceleration of poverty reduction (TNP2K) released the number of child workers in Lampung until 2012 reached 4 thousand. That problem was interesting to do research with regard to how the legal instruments sitting in protecting child workers, what efforts are undertaken by local authorities in Lampung province to protect child workers and the challenges faced in giving protection against child labor. Based on research conducted with the normative approach which is done by examining the legal aspects relating to the legal protection of child workers suggest that many settings have legal protection against child labor in Indonesia and in particular in the province of Lampung is set in Regulation No. 4 Lampung Provinces in 2008 About the service of the rights of the child. Protective measures against child labor include the aspects of legal protection, the protection of economic, social and technical protection. The efforts that have been undertaken by the regional Government of the province of Lampung in protecting child workers is by pulling the child workers in the province of Lampung from environmental work to return was educated at the school. Obstacles that occur in the field more because many workers' children scattered in remote areas that are difficult to do logging, monitoring, and coaching for child workers. So it is recommended that local government existing regulations optimize and conduct cooperation with all the parties to carry out protection and address the problem of child workers in the area.